The Pragmatic Function of Speech for Elementary Students: Indonesian Teaching in Australia - Aurora Adina Cholomeischi; Tudor Colomeischi; Kordula Schulze; Setiawan Edi Wibowo (Jurnal Prima Edukasia, 2023)
This study aimed to describe the pragmatic function of an Indonesian language teaching in Australia and describe the speech act strategies used by foreign teachers to teach Indonesian in Australia. It employs a descriptive qualitative method with a case study approach to the pragmatic function construction in the classroom context. The data are negatively-constructed speeches of a teacher and students who join an Indonesia language learning program, The Apec Lesson Study Project, in Australia. Data are collected through documentation with extended techniques, listening, and recording. Meanwhile, the data are analyzed by using a method of padan pragmatics. The research results show that the pragmatic functions in Indonesian language teaching in Australia can be estimated into various categories and subcategories of speech acts: (1) combinative speech act, manifested into sub-speech acts asking-praising; and (2) directive speech act, manifested into sub-speech acts asking. These findings show how materials, methods, techniques are combined with speech constructions that are appropriate to the student's level. Meanwhile, the speech act strategy used by foreign teachers is a direct literal speech act strategy.